Do Better-Connected CEOs Innovate More? - Faleye, Olubunmi; Kovacs, Tunde; Venkateswaran, Anand (Journal of Financial and Quantitative Analysis, 2014)
Abstract We present evidence suggesting that chief executive officer (CEO) connections facilitate investments in corporate innovation. We find that firms with better-connected CEOs invest more in research and development and receive more and higher quality patents. Further tests suggest that this effect stems from two characteristics of personal networks that alleviate CEO risk aversion in investment decisions. First, personal connections increase the CEO’s access to relevant network information, which encourages innovation by helping to identify, evaluate, and exploit innovative ideas. Second, personal connections provide the CEO with labor market insurance that facilitates investments in risky innovation by mitigating the career concerns inherent in such investments.